Metaheuristics for solving facility layout problems: concepts and trends - Nordin, N. N.; Zainuddin, Z. M.; Kuan, Yew Wong (Universiti Teknologi Malaysia, Skudai, Malaysia, 2007)
In computer science and mathematical optimization, a metaheuristic is a higher-level procedure or heuristic designed to find, generate, or select a heuristic (partial search algorithm) that may provide a sufficiently good solution to an optimization problem, especially with incomplete or imperfect information